Analysis of Quraniyyah Mufradat Content in Basic Arabic Language Textbooks - Imam Fuadi; Sri Putrianingsih (Institut Studi Islam Muhammadiyah Pacitan, 2026)
This study aims to analyze the vocabulary in the Arabic language textbook for grade IV of Madrasah Ibtidaiyah published by the Ministry of Religious Affairs of the Republic of Indonesia by reviewing its suitability to Qur'anic values. The research method used is qualitative with a content analysis approach. The research data is in the form of vocabulary vocabulary contained in several chapters in the textbook. The results of the study show that the vocabulary presented in the textbook is arranged contextually and is close to the daily lives of students, thus facilitating the gradual understanding of Arabic vocabulary. In addition, the analyzed vocabulary contains Qur'anic values ​​that are reflected through the meaning of vocabulary and the context of its use, such as an attitude of gratitude, responsibility, social concern, and love for the homeland. Based on the results of the analysis, it can be concluded that the vocabulary in the Arabic language textbook for grade IV of Madrasah Ibtidaiyah is in accordance with the objectives of learning Arabic in Madrasah Ibtidaiyah and supports the formation of students' Islamic character. Thus, this textbook is relevant to be used as a source for learning Arabic at the Madrasah Ibtidaiyah level.